2021
DOI: 10.3389/fphar.2021.682890
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Direct Oral Anticoagulants in Patients With Non-Valvular Atrial Fibrillation: A Cross-National Comparison in Six European Countries (2008–2015)

Abstract: Aims: To describe and compare the adherence to different direct oral anticoagulants (DOACs) in eight European databases representing six countries.Methods: Longitudinal drug utilization study of new users (≥18 years) of DOACs (dabigatran, rivaroxaban, apixaban) with a diagnosis of non-valvular atrial fibrillation (2008–2015). Adherence was examined by estimating persistence, switching, and discontinuation rates at 12 months. Primary non-adherence was estimated in BIFAP and SIDIAP databases.Results: The highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
2
8
1
Order By: Relevance
“…Differences in persistence to individual NOACs were in line with previous studies, which have demonstrated higher persistence to apixaban than to rivaroxaban or dabigatran ( 8 , 11 , 13 – 15 , 17 , 24 , 34 , 39 , 40 ), except for one study ( 41 ) in which persistence to rivaroxaban was highest. Likewise, other studies also observed predominant switching of dabigatran followed by rivaroxaban ( 30 , 39 41 ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Differences in persistence to individual NOACs were in line with previous studies, which have demonstrated higher persistence to apixaban than to rivaroxaban or dabigatran ( 8 , 11 , 13 – 15 , 17 , 24 , 34 , 39 , 40 ), except for one study ( 41 ) in which persistence to rivaroxaban was highest. Likewise, other studies also observed predominant switching of dabigatran followed by rivaroxaban ( 30 , 39 41 ).…”
Section: Discussionsupporting
confidence: 89%
“…Differences in persistence to individual NOACs were in line with previous studies, which have demonstrated higher persistence to apixaban than to rivaroxaban or dabigatran ( 8 , 11 , 13 – 15 , 17 , 24 , 34 , 39 , 40 ), except for one study ( 41 ) in which persistence to rivaroxaban was highest. Likewise, other studies also observed predominant switching of dabigatran followed by rivaroxaban ( 30 , 39 41 ). Frequent switching and discontinuation of dabigatran may be due to its high dependency on renal clearance, specific side effects such as dyspepsia, longest market approval (resulting in increased switching when other NOACs became available) ( 40 ), twice-daily dosing regimen, and dabigatran being administered in capsules sensitive to moisture which should not be opened or repackaged to other dispensing systems ( 1 , 11 , 18 , 34 , 39 42 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Also diverse studies, including some conducted by our group ( Giner-Soriano et al, 2016 ; 2020 ; Gomez-Lumbreras et al, 2018 ), have described the clinical profile of OAC-users ( Giner-Soriano et al, 2016 ; Rodríguez-Mañero et al, 2017 ), for instance Rodríguez-Mañero et al described different clinical characteristics and outcomes in octogenarians with AF to those in younger people; the adequacy of the prescription ( Dalmau Llorca et al, 2021 ), reporting inadequate OAC prescriptions in up to 67.6% of the cases; or the adherence and persistence to the treatment, using different methods and finding different compliance levels ( Hurtado-Navarro et al, 2018 ; Banerjee et al, 2020 ; Sabaté et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%